Does Human Factor Contribute to Mining Accidents? A Systematic Literature Review Approach - Siti Noraishah, Ismail; Azizan, Ramli (Springer, 2021)
Human factor always has been debated as the key factor contributes to industrial accidents such as manufacturing, construction and many more. However, there are lack of studies globally within this research to review and prove the human factor is a primary cause of accidents at mining industry. The objective of this systematic literature review (SLR) study is to investigate the dominant factor contributes to mining accidents by applying a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Three main themes and fifteen subthemes have been developed based on 25 selected articles from Scopus database. The findings showed the organizational factor is the most dominant contributor to mining accidents (53%) followed by human factor (27%) and situational factor (20%). In conclusion, this finding hopefully could facilitate mine owners to improve organizational safety concern and provide a healthy safety culture in reducing mining accidents in future.